PERBANDINGAN PARTISIPASI POLITIK MAHASISWA UNIVERSITAS RIAU TERHADAP PEMILIHAN UMUM SERENTAK TAHUN 2019 - Andre Naldo Junius Pratama; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The simultaneous election in 2019 cannot be separated from the decision of the Constitutional Court (MK) Number 04/PUU-XI/2013. According to the Constitutional Court the urgency of holding simultaneous elections is to be more efficient both in terms of time and cost, but it will also reduce time wastage and reduce conflict or horizontal friction in society, and in accordance with original intent and systematic interpretation of article 22 E paragraph 2 of the 1945 Constitution. However, this simultaneous election has several weaknesses in terms of voters, as a result of the large variety of choices that must be chosen by voters both president, vice president, DPR, provincial DPRD, regency/city DPRD and DPD, so that many voters do not know the capacity of political choices the voter chooses. The formulation of the problems in this study are (1) how does the University of Riau students' political participation compare between the presidential and vice presidential elections with the legislative elections in 2019?This study aims to (1) Identify, process, and analyze data, and describe and provide an explanation of the political participation of students of Riau University between the presidential and vice presidential elections with the legislative elections in the simultaneous general elections in 2019. This research is a type of descriptive research and explanation using a quantitative approach. Data collection techniques in this study used a field survey technique by taking samples of 99 people from Riau University students, the margin of error was 10%, the data analysis used was quantitative analysis.The results of the study concluded that the political participation of Riau University students towards the presidential and vice presidential elections and the 2019 legislative elections was considered low with an average score recapitulation of 22.7%. While based on the output of the "statistical test", it is known that Asymptotic Significance (2 tailed) is worth 0,000. Because the value of 0,000 is smaller than <0.10, it can be concluded that the "hypothesis is accepted". This means that there is a comparison of the political participation of Riau University students between the presidential and vice presidential elections with the 2019 legislative elections. The comparison is in the category of political participation by Riau University students, namely at the campaign stage and simultaneous election results in 2019. For the category of university student political participation Riau with the 2019 presidential and vice presidential elections was 77.3% in the 'high' category, while for the University of Riau student political participation category in the 2019 legislative elections it was 7.5%, with a 'very low' category. Keywords: Student Political Participation, Simultaneous Elections.